A Comprehensive Model for Developing Salafi and Khalafi Islamic Boarding School Education - Aulalia, Liatul Maula; Fauzi, Ahmad; Shobirin, Shobirin (Al-Qalam Institue, 2025)
Islamic boarding schools as one of the educational institutions, are recognized to have a significant role in raising and developing the world of education. Islamic boarding schools are also believed to be an alternative for solving various educational problems that occur today. Islamic boarding schools that exist today have generally experienced changes from the impact of modernization. One of the Islamic boarding schools that uses a modern education system is the Islamic Boarding School located in Kalikajar Paiton which implements the Salafiyah and Kholafiyah education systems. Therefore, researchers are interested in examining how the Integrated Education Development Model Between Salafiyah and Kholafiyah. The aim is to find out how the strategy for developing salafiyah and kholafiyah education is at Islamic Boarding School, Kalikajar Paiton. This research is a qualitative descriptive study. And in collecting data, researchers use observation, interview and documentation methods. While for the analysis, researchers use qualitative descriptive analysis techniques, namely in the form of written or oral data from people and observed behavior. The results of the study obtained that the strategy for developing the education system carried out at Islamic Boarding School through formal education programs and religious education.